A Triply Selective MIMO Channel Simulator Using GPUs. (5th March 2018) - Carrasco-Alvarez, R.; Carreón-Villal, R.; Vázquez Castillo, J.; Ortegón Aguilar, J.; Longoria-Gandara, O.; Castillo Atoche, A.
Abstract : A methodology for implementing a triply selective multiple-input multiple-output (MIMO) simulator based on graphics processing units (GPUs) is presented. The resulting simulator is based on the implementation of multiple double-selective single-input single-output (SISO) channel generators, where the multiple inputs and the multiple received signals have been transformed in order to supply the corresponding space correlation of the channel under consideration. A direct consequence of this approach is the flexibility provided, which allows different propagation statistics to each SISO channel to be specified and thus more complex environments to be replicated. It is shown that under some specific constraints, the statistics of the triply selective MIMO simulator are the same as those reported in the state of art. Simulation results show the computational time improvement achieved, up to 650-fold for an 8 × 8 MIMO channel simulator when compared with sequential implementations. In addition to the computational improvement, the proposed simulator offers flexibility for testing a variety of scenarios in vehicle-to-vehicle (V2V) and vehicle-to-infrastructure (V2I) systems.